A tailored treatment strategy: a modern approach for stroke prevention in patients with atrial fibrillation. (22nd March 2016) - Lip, G. Y. H.; Potpara, T.; Boriani, G.; Blomström‐Lundqvist, C.
Abstract: The main priority in atrial fibrillation (AF) management is stroke prevention, following which decisions about rate or rhythm control are focused on the patient, being primarily for management of symptoms. Given that AF is commonly associated with various comorbidities, risk factors such as hypertension, heart failure, diabetes mellitus and sleep apnoea should be actively looked for and managed in a holistic approach to AF management. The objective of this review is to provide an overview of modern AF stroke prevention with a focus on tailored treatment strategies. Biomarkers and genetic factors have been proposed to help identify 'high‐risk' patients to be targeted for oral anticoagulation, but ultimately their use must be balanced against that of more simple and practical considerations for everyday use. Current guidelines have directed focus on initial identification of 'truly low‐risk' patients with AF, that is those patients with a CHA2 DS2 ‐VASc [congestive heart failure, hypertension, age ≥75 years (two points), diabetes mellitus, stroke (two points), vascular disease, age 65–74 years, sex category] score of 0 (male) or 1 (female), who do not need any antithrombotic therapy. Subsequently, patients with ≥1 stroke risk factors can be offered effective stroke prevention, that is oral anticoagulation. The SAMe‐TT2 R2 [sex female, age <60 years, medical history (>2 comorbidities), treatment (interacting drugs), tobacco use (two points), race non‐Caucasian (two points)] score can help physicians make informed decisions on those patients likely to do well on warfarin (SAMe‐TT2 R2 score 0–2) or those who are likely to have a poor time in therapeutic range (SAMe‐TT2 R2 score >2). A clinically focused tailored approach to assessment and stroke prevention in AF with the use of the CHA2 DS2 VASc, HAS‐BLED [hypertension, abnormal renal/liver function (one or two points), stroke, bleeding history or predisposition, labile international normalized ratio, elderly (>65 years) drugs/alcohol concomitantly (one or two points)] and SAMeTT2 R2 scores to evaluate stroke risk, bleeding risk and likelihood of successful warfarin therapy, respectively, is discussed. Abstract : Content List – Read more articles from the symposium: Atrial fibrillation ‐ from atrial extrasystoles to atrial cardiomyopathy. What have we learned from basic science and interventional procedures